The Relationship of Self Determination with Student Learning Outcomes of Skipping at SMAN 5 Pariaman - Alni Fauzana; Firman Firman (Universitas Negeri Padang, 2019)
Self-determination is an ability possessed by an individual in determining his future destiny that is not resigned to conditions that do not allow. If students are resigned to the conditions they experience will have a negative impact on learning outcomes in school and their future. In reality, it was found out that there were many students who did not think about their future by frequently skipping class during school in the form of frequent absences after recess, not following the learning process in class without clear explanation. This study aims to: (1) describe the level of self-determination of students truant, (2) describe the results of truant student truancy, (3) test whether there is a significant relationship between student self-determination and student learning truant. This research is a descriptive correlational type of research with quantitative methods. The research subjects were students skipping class XI and XII at Pariaman 5 High School in the 2018/2019 school year as many as 73 people who were determined by purposive random sampling technique. The instrument used was the self determination questionnaire. Data were analyzed with descriptive and correlational statistical techniques with the help of the SPSS 20.0 for Windows software program. The results revealed that (1) the level of self-determination of truant students was in the high enough category, (2) the condition of student learning outcomes was in the quite high category, and (3) there was a significant relationship between self-determination (self determination) with student learning outcomes ditching with a correlation coefficient of 0.738 and has a strong relationship.